MEDIA PEMBELAJARAN BERBASIS PERMAINAN LUDO MATERI SISTEM PENCERNAAN PADA PEMBELAJARAN IPAS KELAS V SEKOLAH DASAR - Aulia Nur Rahmawati; Henry Januar Saputra; Wawan Priyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The background of the research is the lack of learning media used in learning and the absence of game-based learning media. This study aims to produce learning media based on ludo games on the digestive system in grade V Elementary School IPAS learning. The research uses Research and Development (RnD) with the ADDIE model development model which has 5 stages, namely analysis, design, development, implementation, evaluation. The test subjects were fifth grade students of SDN Sembungharjo 02 and SDN Karangroto 01. The data collection techniques used were interviews, observations, and questionnaires. The research instruments used were observation sheets, interview sheets, teacher and student needs questionnaires, media and material validation questionnaires, and teacher and student response questionnaires. Data analysis techniques in this study used quantitative descriptive data analysis and qualitative descriptive data analysis. The results showed that the ludo game-based learning media was very valid with a media validation score of 96.25% and material validation of 96.88%. The practicality of the media is categorized as very practical by teachers by 100% and students by 98,11%. Thus, learning media based on ludo games can be said to be valid and practical, and can be used optimally in delivering human digestion material.